Intrahousehold Decision Making and Fertility - Matthias Doepke; Fabian Kindermann (Institute for the Study of Labor (IZA), 2014)
The economic theory of fertility choice builds predominantly on the unitary model of the household, in which there is a single household utility function and potential intra-household disagreement is abstracted from. Empirical evidence suggests, however, that many (potential) mothers and fathers disagree on whether to have children, on how many children to have, and on when to have them. In this paper, we review existing work that brings models of intrahousehold conflict and bargaining to bear on fertility choice, and we point out promising future directions for this line of research.
Keywords: D13; J12; J13; 330; fertility; bargaining; child care; limited commitment